Where Is the Chilean Peso Headed? (Observatorio Económico, 2009)
Predicting the 13.8% fall in the nominal exchange rate of the US dollar this year would have been, at best, wishful thinking (and, at worst, fraudulent advice). There will always be someone who gets the forecast right, but there is no way of knowing whether that is brilliance or luck. Continue reading...
Keywords: Chilean peso; CLP; dollar